The informal economy revisited: Examining the past, envisioning the future - Martha Alter Chen; Françoise J. Carré (Routledge, 2020)
This landmark volume brings together leading scholars in the field to investigate recent conceptual shifts, research findings and policy debates on the informal economy. Researchers, practitioners and policy makers will find this book an invaluable guide to the significance of the informal economy.
Keywords: 330; economics; development; social inequality; labour economics; development economics; African economics; culture and development; Informelle Wirtschaft; Schwarzarbeit; Atypische Beschäftigung; Sozialstandards; Sozialpolitik; Arbeitsrecht; Heimarbeit; Ambulanter Handel; Entwicklungsländer